INTEGRASI STEAM DALAM KARYA 3 DIMENSI : STUDI SIKAP KOLABORASI MELALUI TEKNIK STEMPEL - Susanti, Atika; Ramadhanti, Adinda Asri (DIRASATUL IBTIDAIYAH, 2026)
AbstractVisual arts learning in elementary schools not only plays a role in developing creativity but also serves as an important medium for character education, particularly in fostering collaborative attitudes. This study examines the integration of the STEAM approach in three-dimensional visual arts learning using natural material stamping techniques, as well as exploring the development of collaborative attitudes among fourth-grade students during project-based collaborative learning. The study employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The learning activities involved observing the properties and textures of natural materials (Science), using simple tools (Technology), designing three-dimensional structures (Engineering), exploring form and aesthetics (Arts), and measuring patterns and proportions (Mathematics). The results indicate that the STEAM integration successfully fostered six indicators of collaboration: active participation, productive work, responsibility for one’s role, flexibility in adapting, mutual respect, and commitment to completing the project. Although the learning activity was conducted only once, students were able to collaborate intensively, engage in discussions, overcome technical challenges, and produce work according to the objectives and timeline. These findings confirm that project-based STEAM approaches are effective in strengthening students’ collaborative attitudes. It is recommended that teachers use easily accessible natural materials, prepare simple tools and supplies, create easily understandable patterns, and provide paint palettes to ensure efficiency and orderliness in visual arts learning.Keywords: STEAM, Three-Dimensional, Natural Materials, Collaborative Attitudes. Abstrak Pembelajaran seni rupa di sekolah dasar tidak hanya berperan dalam pengembangan kreativitas, tetapi juga menjadi sarana penting dalam pendidikan karakter, khususnya dalam menumbuhkan sikap kolaboratif. Penelitian ini mengkaji integrasi pendekatan STEAM dalam pembelajaran seni rupa tiga dimensi melalui teknik stempel berbahan alam, serta mengeksplorasi pembentukan sikap kolaboratif siswa kelas IVA SD selama proses pembelajaran berbasis proyek kolaboratif. Penelitian ini menggunakan metode kualitatif deskriptif. Teknik pengumpulan data meliputi: observasi, wawancara, dan dokumentasi. Pembelajaran melibatkan pengamatan sifat dan tekstur bahan alam (Science), penggunaan alat sederhana (Technology), perancangan struktur tiga dimensi (Engineering), eksplorasi bentuk dan estetika (Arts), serta pengukuran dan pola (Mathematics). Hasil penelitian menunjukkan integrasi STEAM berhasil membentuk enam indikator kolaborasi yaitu: aktif berpartisipasi, produktif bekerja, bertanggung jawab terhadap peran, fleksibel menyesuaikan diri, saling menghargai, dan berkomitmen menyelesaikan proyek. Meskipun pembelajaran hanya berlangsung satu kali, siswa mampu bekerja sama intensif, berdiskusi, mengatasi kendala teknis, dan menghasilkan karya sesuai tujuan dan waktu yang ditetapkan. Temuan ini menegaskan bahwa pendekatan STEAM berbasis proyek efektif memperkuat aspek sikap kolaboratif siswa. Disarankan guru menggunakan bahan alam yang mudah dijangkau, menyiapkan alat dan bahan sederhana, membuat pola yang mudah dipahami, serta menyediakan palet cat untuk efisiensi dan keteraturan penggunaan cat dalam pembelajaran seni rupa.Kata Kunci: STEAM, Tiga Dimensi, Bahan Alam, Sikap Kolaborasi.